How does strength use relate to burnout among Chinese healthcare professionals? Exploring the mediating roles of beliefs about stress and basic psychological needs satisfaction - Chengzhi Bai; Jie Ma; Baoyu Bai (BMC, 2024)
Abstract Background The prevalence of burnout among healthcare workers remains chronically high. Former studies have indicated that strength use is a promising approach to reduce burnout. However, relatively little is known about the psychological mechanisms underlying the ability of strength use to reduce burnout, especially among healthcare workers. Aim This study sought to examine the link between strength use and burnout in Chinese healthcare workers, and to explore the mediating roles of beliefs about stress and basic psychological needs satisfaction in that relationship. Methods This study was conducted in two time periods, from September to October 2020 and from February to September 2022. A total of 812 healthcare workers completed a multi-section questionnaire. Results Strength use was negatively associated with burnout and negative stress beliefs, and positively associated with positive stress beliefs, control beliefs, and basic psychological needs satisfaction. Moreover, negative stress beliefs, control beliefs, and basic psychological needs satisfaction fully mediated the relationship between strength use and burnout. Furthermore, effect contrasts revealed that the mediating effect of basic psychological needs satisfaction was stronger than that of negative stress beliefs and control beliefs. Conclusion Our findings revealed that negative stress beliefs, control beliefs, and basic psychological needs satisfaction act as mediators in the association of strength use with burnout. Furthermore, basic psychological needs satisfaction plays a more important mediating role than negative stress beliefs and control beliefs in the strength use-burnout relationship.